Effect of traditional Chinese medicine on postoperative depression of breast cancer: a systematic review and meta-analysis - Wang, Yan; Liu, Suying; Zhang, Ying; Zhu, Guanghui; Wang, Heping; Xu, Bowen; Xie, Yi; Yang, Shuhan (Frontiers in Pharmacology, 2023)
Background: Depression is one of the common complications in patients with postoperative breast cancer (BC). Conventional therapies for postoperative depression of BC always have modest treatment outcomes and undesirable side effects. Clinical practice and many studies have shown that traditional Chinese medicine (TCM) has a good effect on postoperative depression of BC. This meta-analysis aimed to assess the clinical effect of TCM as an add-on treatment for postoperative depression of BC. Methods: A systematic and thorough search was conducted on eight online electronic databases up to 20 July 2022. The control group received conventional therapies, and intervention groups received what control groups received plus TCM treatment. Review Manager 5.4.1 was used for statistical analysis. Results: Nine RCTs involved 789 participants who met the inclusion standards. The results showed the intervention group was better at decreasing the score of the Hamilton rating scale for depression (HAMD) (mean difference, MD = −4.21, 95% CI −5.54 to −2.88) and the self-rating depression scale (SDS) (MD = −12.03, 95% CI −15.94 to −8.13), improving clinical efficacy (RR = 1.25, 95% CI 1.14–1.37), increasing the levels of 5-hydroxytryptamine (5-HT) (MD = 0.27, 95% CI 0.20–0.34), dopamine (DA) (MD = 26.28, 95% CI 24.18–28.77), and norepinephrine (NE) (MD = 11.05, 95% CI 8.07–14.04), and influencing the immune index, including the levels of CD3+ (MD = 15.18, 95% CI 13.61–16.75), CD4+ (MD = 8.37, 95% CI 6.00–10.74), and CD4+/CD8+ (MD = 0.33, 95% CI 0.27–0.39). The level of CD8+ (MD = −4.04, 95% CI −11.98 to 3.99) had no obvious difference between the two groups. Conclusion: The meta‐analysis stated that a therapeutic regimen involving TCM could better improve the depression status in postoperative BC.